ANALISIS PERBANDINGAN HARGA SAHAM PADA PT BANK CENTRAL ASIA TBK SEBELUM DAN SESUDAH PANDEMI COVID-19 DI INDONESIA - Elis Novianti; Ardi Hidayat; Slamet Gunadi (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This research was conducted with the aim of analyzing the impact of the Covid-19 pandemic on the capital market, especially on stock investment because stocks are an important factor to see the value of the company or it can also be said to be a tool for investor consideration. The research method used in this study is qualitative which aims to obtain a complete picture of various things based on human perception. This research is comparative by using a comparative study (comparative study) conducted by comparing the share price and earnings per share (EPS) of PT Bank Central Aaia Tbk before with after the Covid-19 pandemic. Pt Bank Central Aaia Tbk's closing price and earnings per share (EPS) data taken from www.idx.co.id are data on closing stock prices and EPS per quarter for the 2016-2018 period before and 2019-2021 after the Covid-19 pandemic.Normality test results show that the significance of share price and earnings per share before and after the Covid-19 pandemic is 0.534, respectively,   0.000, 0.534 and 0.127. Because the data is not normally distributed, the difference test for PT Bank Central Asia Tbk's share price and earnings per share before and after the Covid-19 pandemic uses a nonparametric test, namely the Wilcoxon test. The results of the study using the nonparametric test, namely the Wilcoxon test, showed Asymp. Sig. (2-tailed) between the share price and earnings per share of PT Bank Central Asia Tbk before and after the Covid-19 pandemic was 0.034 each. That is to say the value of Asymp. Sig. (2-tailed) 0.034 is less than 0.05 (0.034 ≤ 0.05). This value shows that H1 is accepted and H0 is rejected, meaning that there is a significant difference between the share price and the earnings per share condition of PT Bank Central Asia Tbk before and after the Covid-19 pandemic